Designing Special Nonmetallic Superalkalis Based on a Cage-like Adamanzane Complexant - Ye, Ya-Ling; Pan, Kai-Yun; Ni, Bi-Lian; Sun, Wei-Ming (Frontiers in Chemistry, 2022)
To examine the possibility of using cage-like complexants to design nonmetallic superalkalis, a series of X@36adz (X = H, B, C, N, O, F, and Si) complexes have been constructed and investigated by embedding nonmetallic atoms into the 36adamanzane (36adz) complexant in this work. Although X atoms possess very high ionization energies, these resulting X@36adz complexes possess low adiabatic ionization energies (AIEs) of 0.78 eV 5.28 eV. In particular, the AIEs of X@36adz (X = H, B, C, N, and Si) are even lower than the IE (3.89 eV) of Cs atom, and thus, can be classified as novel nonmetallic superalkalis. Moreover, due to the existence of diffuse excess electron in B@36adz, this complex not only possesses pretty low AIE of 2.16 eV, but also exhibits a remarkably large first hyperpolarizability (β0) of 1.35×106 au, indicating that it can also be considered as a new kind of NLO molecule. As a result, this study provides an effective approach to achieve new metal-free species with excellent reducing capability by utilizing cage-like organic complexants as building blocks.